2006
DOI: 10.1016/j.tsf.2005.07.192
|View full text |Cite
|
Sign up to set email alerts
|

Properties of MoNxOy thin films as a function of the N/O ratio

Abstract: The main purpose of this work consists on the preparation of single layered molybdenum oxynitride, MoN x O y . The films were deposited on steel substrates by dc reactive magnetron sputtering. The depositions were carried out from a pure Mo target varying the flow rate of reactive gases, which allowed tune the crystallographic structure between insulating oxides and metallic nitrides and consequently electronic, mechanical and optical properties of the material. X-ray diffraction (XRD) results revealed the occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The d-MoN phase is a metastable state and has a higher lattice constant as a result of the nitrogen incorporation [16].…”
Section: Resultsmentioning
confidence: 99%
“…The d-MoN phase is a metastable state and has a higher lattice constant as a result of the nitrogen incorporation [16].…”
Section: Resultsmentioning
confidence: 99%
“…MoN x layers have been deposited using a range of methods and processing parameters, leading to different compositions and phases. More specifically, reactive DC sputtering [23][24][25]28,[31][32][33][34][35][36][37][38][39] yields MoN x with x = 1.08 in the γ phase (with a small amount of possible δ phase) using 60 sccm of N 2 gas flow and 55 sccm of Ar gas flow as well as a -50 V substrate bias [31], x = 0-0.54 in the γ phase using 0-26% of N 2 process gas [33] and also from 0-0.35 in the γ phase with varying N 2 / (Ar + N 2 ) gas ratio [37]. RF sputtering [40][41][42] results in x = 0.49-0.67 in the γ phase [41], x = 0.55-0.9 in the γ phase and x = 0.9-1.02 in the δ phase [40], and x = 0.9-1.8 in the B1-MoN phase, which can be described as a cubic variant of the γ phase [42].…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal oxynitride thin films possess the main advantage of tuning the oxygen/nitrogen content, thus leading to films suited for a large number of applications. The effect of oxygen addition to transition metal nitrides on the mechanical properties has been previously reported for molybdenum compounds [10], titanium compounds [11][12][13][14] and zirconium compounds [15][16][17], among others.…”
Section: Introductionmentioning
confidence: 81%
“…Molybdenum oxynitride thin films, studied by J. Barbosa et al [10], using DC reactive magnetron sputtering, revealed a strong decrease of the hardness, from~25 GPa to values lower than 5 GPa, and of Young's modulus, from~275 GPa to~50 GPa, with the increase of oxygen content in the films. Titanium oxynitride thin films seem to exhibit a similar trend concerning the mechanical properties as a function of oxygen content.…”
Section: Introductionmentioning
confidence: 98%